Exploring environmental constraints that hinder the physical activity of middle school girls in daily life: Photo-Voice - GyuIl Lee (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to explore environmental constraints that hindered the physical activity of female students in daily life, and then to provide alternatives to improve the problems based on the social ecological model. Methods Research participants were twelve female students to be selected in two schools(Norang, Parang middle school), the process of data collection(orientation, photovoice implementation, focus group interview) and analysis(choosing a photo, contextualizing, subjecting) were conducted according to the Photo-voice. Results The constraints of physical activity in daily life were categorized on 'playground as like a desert'(leisure domain), 'space of recess and in-active play'(family domain), 'transportation replaced by mom and dad car'(transportation domain), 'space of the only exercise as well as reproduction of gender discrimination'(school domain). Conclusions The environmental constraints were analyzed as academic, physical, daily living, socio-cultural environment. Lastly, alternatives for promoting physical activity of female student were proposed in the level of organization, community, public policy based on the social ecological model.